2022
DOI: 10.1007/s11694-022-01417-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential of milling byproducts for the formulation of health drink and detox tea-substitute

Abstract: Due to pandemic situation, a sudden demand of healthy and immune booster products has risen to get rid of infections like Covid-19. The aim of this study is to develop novel health drink and beverages using plant-based byproducts like orange peel, milling byproducts (chickpea husk, rice bran, broken rice, wheat bran). Byproducts were processed by using different culinary processes such as, soaking, blanching, roasting, natural air-drying. Proximate composition along with minerals, antioxidants, Vitamin-C of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Pea pods were blanched for 2-10 min at 95-100 • C (Hanan et al, 2020;Rudra et al, 2020), whereas common bean pods were disinfected with polyhexamethylene biguanide rather than blanching (Martínez-Castaño et al, 2020). Chickpea byproducts were soaked for 1 h and then blanched (Chakraborty et al, 2022) for beverage applications or boiled for 10 min (Beniwal & Jood, 2015). After blanching, the water is removed by air drying, usually at 42-60 • C for 3-8 h. Martínez-Castaño et al (2020) compared vacuum drying with air dying at 60 • C for 8 h. The study revealed that the color, water-holding capacity, and oil-holding capacity were similar for both methods, except for the antioxidant levels.…”
Section: Flourmentioning
confidence: 99%
See 4 more Smart Citations
“…Pea pods were blanched for 2-10 min at 95-100 • C (Hanan et al, 2020;Rudra et al, 2020), whereas common bean pods were disinfected with polyhexamethylene biguanide rather than blanching (Martínez-Castaño et al, 2020). Chickpea byproducts were soaked for 1 h and then blanched (Chakraborty et al, 2022) for beverage applications or boiled for 10 min (Beniwal & Jood, 2015). After blanching, the water is removed by air drying, usually at 42-60 • C for 3-8 h. Martínez-Castaño et al (2020) compared vacuum drying with air dying at 60 • C for 8 h. The study revealed that the color, water-holding capacity, and oil-holding capacity were similar for both methods, except for the antioxidant levels.…”
Section: Flourmentioning
confidence: 99%
“…Bread containing chickpea husks reached 110 mg GAE/100 g (Niño-Medina et al, 2019) and bread containing common bean seed coats reached 31.28 mg cyanidin-3-glucoside/100 g dry weight (DW; Chávez-Santoscoy et al, 2016). Recently, Chakraborty et al (2022) developed health drinks from chickpea in which the hulls had a TPC value of ∼400 mg GAE/100 g. Pods have been used in pectin and alginate beads as antioxidant ingredients, and the TPC of cowpea pod hydrogels was 22-28 mg/100 mL (Traffano-Schiffo et al, 2020). TPC data for soup, mayonnaise, meat products, and mildly treated snacks would be useful to understand the interactions of the food matrix and to evaluate the shelf life of formulated products.…”
Section: Total Phenolic Content: Ingredients and Foodsmentioning
confidence: 99%
See 3 more Smart Citations